Gambaran Karakteristik Akseptor KB Suntik 3 Bulan dengan Amenorea Sekunder di BPM Bidan “S” Curug Tangerang 2017 - Putri Handayani Setyaningsih (STIKes Kharisma Persada, 2019)
Based on the survey results of January - April 2017 aksetor number of injections 3 months in Midwives BPM